Mucosal Administration of Cycle-Di-Nucleotide-Adjuvanted Virosomes Efficiently Induces Protection against Influenza H5N1 in Mice - Ebensen, Thomas; Debarry, Jennifer; Pedersen, Gabriel K.; Blazejewska, Paulina; Weissmann, Sebastian; Schulze, Kai; McCullough, Kenneth C.; Cox, Rebecca J.; Guzmán, Carlos A. (Frontiers in Immunology, 2017)
The need for more effective influenza vaccines is highlighted by the emergence of novel influenza strains, which can lead to new pandemics. There is a growing population of susceptible subjects at risk for severe complications of influenza, such as the elderly who are only in part protected by current licensed seasonal vaccines. One strategy for improving seasonal and pandemic vaccines takes advantage of adjuvants to boost and modulate evoked immune responses. In the present study we examined the capacity of the recently described adjuvant cyclic di-adenosine monophosphate (c-di-AMP) to serve as an adjuvant for improved mucosal influenza vaccines, and induce effective protection against influenza H5N1. In detail, c-di-AMP promoted (i) effective local and systemic humoral immune responses, including protective HAI titers, (ii) effective cellular responses, including multifunctional T cell activity, (iii) induction of long-lasting immunity, and (iv) protection against viral challenge. Furthermore, we demonstrated the dose-sparing capacity of the adjuvant as well as the ability to evoke cross-clade protective immune responses. Overall, our results suggest that c-di-AMP contributes to the generation of a protective cell-mediated immune response required for efficacious vaccination against influenza, which supports the further development of c-di-AMP as an adjuvant for seasonal and pandemic influenza mucosal vaccines.